SISTEM PENJADWALAN MATA PELAJARAN SEKOLAH DASAR BERBASIS WEB - Aris Fajrianto; Ilhamsyah Ilhamsyah; Rahmi Hidayati (Coding Jurnal Komputer dan Aplikasi, 2021)
Schedule is very important and becomes a reference when teaching and learning activities take place. Clashes on subject schedules are a common problem that occurs in teaching and learning activities in schools. To minimize the occurrence of clashes between schedules, there are several things that must be considered in making course schedules, including the mapping of teachers who teach, the allocation of time slots, the space available in the school, as well as rules and restrictions on the schedule that must not be violated. In making or compiling a schedule, accuracy and time are also required so that the schedule does not conflict when teaching and learning activities are carried out. This application was made with the aim of making it easier for the school in making subject schedules by minimizing the occurrence of clashes between schedules. Applications built on a web basis using the Laravel and Vue.js frameworks. This application requires input data in the form of teacher teaching allocations and time slot allocations. The output data in this application is a schedule of subjects that are displayed based on class. Keyword: Schedule, Subject, School, Clashes, Web.